The impact of board internationalization on earnings management - Reggy Hooghiemstra; Niels Hermes; Lars Oxelheim; Trond Randøy (Research Institute of Industrial Economics (IFN), 2015)
Prior literature shows that choices regarding board composition are associated with earnings management. We add to this literature by examining the effects of the presence of a foreign board member on earnings management. Using a sample of 3,249 firm-year observations representing 586 non-financial listed Nordic firms during 2001-2008, we find that the presence of a non-Nordic, foreign director is associated with significantly higher levels of earnings management. Moreover, we provide preliminary evidence that differences in accounting knowledge drive this effect. Our results suggest that it may not necessarily be beneficial to appoint a foreign director to the board.
Keywords: G34; M16; M41; M52; 330; Earnings management; Board composition; Internationalization; Foreign board member; Accounting knowledge